The effectiveness of the use of animation in Arabic language learning - Norhayati, Che Hat; Mohd Fauzi, Abdul Hamid; Safawati Basirah, Zaid; Shaferul Hafes, Sha'ari (Canadian Center of Science and Education, 2017)
Implementation of animation as an Arabic language teaching aid is an innovation in creating an atmosphere that can influence student achievement. This study aimed to identify the effectiveness of the use of animation in Arabic language teaching and learning among diploma students at Universiti Sultan Zainal Abidin (UniSZA), Terengganu, Malaysia. A total of 66 diploma students were randomly selected and divided into experimental group (n = 33) and control group (n = 33). The results obtained from the data collected from pre-and post-test for each group were analyzed using t-test in SPSS version 17.0. The results showed a significant difference of (t = 8789, df = 64, p <0.05) between the achievement of the experimental group and the control group in the post test. The difference in mean score of the experimental group and the control group was 33.03. This shows that there is significant improvement in Arabic language according to the groups. The difference prove that the use of animation in learning sessions contribute to the achievement of students in the Arabic language. This study advocate the idea that animation applications can be integrated as part of language teaching aid to positively improve student achievement, classroom learning environment and student motivation.